2008
DOI: 10.1016/j.compscitech.2007.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue evaluation and dynamic mechanical thermal analysis of sisal fibre–thermosetting resin composites

Abstract: . Fatigue evaluation and dynamic mechanical thermal analysis of sisal fibre -thermosetting resin composites. Composites Science and Technology, Elsevier, 2009, 68 (3-4), pp.925.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(43 citation statements)
references
References 9 publications
1
42
0
Order By: Relevance
“…In order to solve these problems, the new engineering materials based on all inedible plants-derived materials are strongly required. Meanwhile, the investigation of short natural (plant) fibers, which are banana, falx, hemp, ramie, sisal fiber and so on, reinforced biopolymer composites have attracted more and more in recent decades [3,4]. These natural fiber have some ecological advantages over inorganic fibers such as carbon and glass fibers since they are renewable and can be incinerated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, the new engineering materials based on all inedible plants-derived materials are strongly required. Meanwhile, the investigation of short natural (plant) fibers, which are banana, falx, hemp, ramie, sisal fiber and so on, reinforced biopolymer composites have attracted more and more in recent decades [3,4]. These natural fiber have some ecological advantages over inorganic fibers such as carbon and glass fibers since they are renewable and can be incinerated.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a strong interface is connected with higher dynamic modulus and reduction in stiffness degradation with increasing load cycles and applied maximum stresses and the specific damping capacity had higher values for the composites with poor bonded fibers. In another research, thermosets filled with sisal fibers were tested by Towo et al [11,12] and here also the quality of fiber-matrix adhesion was the main topic of interest when discussing fatigue and dynamical properties. It was found that the effect of chemical treatment on the fatigue life is significantly positive for polyester matrix composites but has much less influence on the fatigue life of epoxy matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of composite materials under cyclic loading, failure is generally associated with the initiation and propagation of cracks in the matrix and the loss of adhesion at the polymer/matrix interface. This aspect of the interface quality between polymer matrix and natural or synthetic fibers have been already investigated [7][8][9][10][11][12] and thus will not be closely discussed in the experimental part of this study. The brittleness of fibers and their cracking, the differences in fiber and matrix mechanical properties are the further factors that influence dynamic and fatigue behavior of a material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as a bridge, silane coupling agents can couple together hydrophilic and hydrophobic materials. Although the treatment is well established with natural fiber composites, its effect on natural fibers has not been extensively studied in natural fiberphenolic foam composites (Colom et al 2003;Pickering et al 2003;Te-fu et al 2005;Towo and Ansell 2008).…”
Section: Introductionmentioning
confidence: 99%